EVIDENCE-GUIDED OPTIMIZATION OF HERBAL FORMULA CHEONG-HWA-BO-UM-TANG USING MULTIPLEX CYTOKINE PROFILING - Lee, Ji Young; Park, Wansu (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Cheong-Hwa-Bo-Um-Tang (CHB) has been traditionally used to treat pharyngolaryngitis and throat inflammation in Korea. However, the anti-inflammatory activity of CHB and the exact component proportion ratio of CHB have not been fully reported. Materials and Methods: This study was conducted to optimize the component proportion ratio of CHB on the basis of experimental evidence using multiplex cytokine profiling assay in LPS-stimulated RAW 264.7 mouse macrophages. Results: The optimized CHB (named Chunhwabun-Cheong-Hwa-Bo-Um-Tang) inhibited the production of NO, IL-6, MCP-1, GMCSF, IL-10, IP-10, VEGF, M-CSF, RANTES, MIP-1β, LIF, LIX, and TNF-α in LPS-stimulated RAW 264.7 mouse macrophages without decreasing cell viability (P<0.05). Chunhwabun-Cheong-Hwa-Bo-Um-Tang consisted of roots of Scrophularia buergeriana, Trichosanthes kirilowii, Anemarrhena asphodeloides, Phellodendron amurense, Angelica gigas, Rehmannia glutinosa, Paeonia japonica, Cnidium officinale, and Glycyrrhiza uralensis (in the ratio of 8: 3: 3: 3: 3: 4: 4: 3: 3). Conclusion: The results of this study indicate that the multiplex cytokine profiling assay could be one of the effective methods for evidence-guided optimization of the component proportion ratio of a traditional herbal formula used for treating excessive inflammation such as the cytokine storm.